Modeling and parametric analysis of the energy generation by the piezoelectric energy harvesters: A case study - Amir Abedanzadeh; Roghayeh Ghasempour; Mohammad Hossein Jahangir (Energy Reports, 2023)
Employing renewable energy resources, such as new harvesting technologies, plays a significant role in reducing fossil fuel defects. One of these technologies is the piezoelectric energy harvester (PEH), which converts the energy generated by mechanical vibrations into electrical energy. This paper remarks on the perspective use of piezoelectric tiles, which is a great stride in commercialization. It can also raise researcher’s awareness and investors’ willingness to use this technology. Besides, this research recommends conducting a sensitivity analysis of the energy produced by these tiles and investigating its various consequences (e.g., emissions and traded energy to the grid), which is considered an innovative approach. This study presents a model to supply the lighting load of a university faculty building using piezoelectric tiles. This research also developed a balance between energy production and consumption modeling, optimization, and sensitivity analyses on energy production by piezoelectric tiles. Our findings revealed that the piezoelectric tiles are able to supply 50% of the lighting load, and it can increase by 80% by doubling the energy production. After doubling the efficiency (providing 80% of the lighting load), the energy that is purchased from the grid decreases by 51.81%, and the energy that is sold to the grid increases by 134.85%. In addition, emissions of pollutants, such as CO2, CO, and NOx, are diminished by 51.77, 51.75, and 51.96%, respectively. The results demonstrate that improvement of efficiency of energy production (α) by 89.73% leads to the purchased and sold energy that equals 345.65 kWh.